2021
DOI: 10.1007/s00500-021-06103-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Hybrid intelligent model for classifying chest X-ray images of COVID-19 patients using genetic algorithm and neutrosophic logic

Abstract: The highly spreading virus, COVID-19, created a huge need for an accurate and speedy diagnosis method. The famous RT-PCR test is costly and not available for many suspected cases. This article proposes a neurotrophic model to diagnose COVID-19 patients based on their chest X-ray images. The proposed model has five main phases. First, the speeded up robust features (SURF) method is applied to each X-ray image to extract robust invariant features. Second, three sampling algorithms are applied to treat imbalanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 70 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…Their suggested model achieved an accuracy of 96% for two-way classification. Basha et al (2021) [ 33 ] reported a neurotrophic model for COVID-19 diagnosis from chest X-ray images with an accuracy of 98.7% for two-way classification.…”
Section: Resultsmentioning
confidence: 99%
“…Their suggested model achieved an accuracy of 96% for two-way classification. Basha et al (2021) [ 33 ] reported a neurotrophic model for COVID-19 diagnosis from chest X-ray images with an accuracy of 98.7% for two-way classification.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the lack of a dataset has driven researchers to do more exploration on the dataset. Therefore, such a Generative Adversarial Network (GAN) technique is needed to overcome the dataset's limitation [6][7][8]. In recent research in the Journal of Radiology, X-ray chest imagery is superior to outclassed lab testing such as PCR or rapid tests.…”
Section: Related Workmentioning
confidence: 99%
“…Generally, for pulling out useful information, edge detection is useful which gives us the detailed information of the object. In the proposed model, Sobel Edge Detection algorithm 46 , 47 , 48 is used which is made up of 3*3 convolutional kernels.…”
Section: Proposed Modelmentioning
confidence: 99%